Settlement-induced bending moments on pile-founded floodwalls. Issue 1 (8th February 2017) - Kokkali, Panagiota; Tessari, Anthony; Abdoun, Tarek; Varuso, Richard; Johnson, Jehu; Filz, George; Reeb, Alexander
Abstract : T-walls are pile-supported floodwalls commonly built in New Orleans. They are founded on long concrete or steel battered piles and include a sheet pile cut off for seepage and gradient control. Since soils in southern Louisiana contain soft and compressible silt and clay, these floodwalls need to be designed to resist flood loads and loads produced by consolidation of soft soil under the weight of new fill. In an attempt to develop a comprehensive T-wall design procedure that appropriately considers field conditions, the United States Army Corps of Engineers New Orleans District partnered with Rensselaer Polytechnic Institute and Virginia Polytechnic Institute and State University. A testing programme was developed to perform centrifuge tests that would provide insight into the mechanisms and magnitudes of settlement-induced bending moments and reliable datasets for validation of numerical models. This paper describes the experimental approach and presents two centrifuge tests with T-walls resting directly on clay. The bending moments on the battered piles significantly increased under the weight of the new fill. With settlement around the piles reaching values of 1·5 m, the bending moments at least doubled over the testing course, with maximum values observed at the top third of the pile length.